The Effect of a Low Degree of Fluorine Substitution on Cotton Fiber Properties - Ofir Aharon Kuperman; Peterson deAndrade; Tanguy Terlier; Jacob Judas Kain Kirkensgaard; Robert A. Field; Filipe Natalio (Macromolecular Materials and Engineering, 2024)
Abstract Cellulose modification often employs chemical processes to tailor its properties and functionalities to fit the demands of a wide range of applications, maximizing its potential as a versatile and sustainable material. From both synthetic and environmental standpoints, one of the ultimate goals is to achieve significant modifications to enhance the end properties of the cellulose while minimizing the number of modified building blocks. The current study demonstrates that a synthetic glucose derivative, 6‐deoxy‐6‐fluoro‐glucose (6F‐Glc), fed into the fertilized cotton ovules, resulted in the accumulation of fluorine inside the cotton fibers with no apparent alteration to their morphology or development. These fibers exhibited a degree of substitution of 0.006, which is 170 times lower than that reported for chemical methods for cellulose modification. However, the physical characterization of the modified fibers showed a surprisingly large impact of this low‐level modification on the cellulose structure (e.g., hydrogen bonding network rearrangement) and a modest increase in the mechanical properties of the fibers. The obtained results exemplify the use of biological systems to introduce low quantities of new functionalities while maximizing the impact on fiber properties.